Estimation of Tensile Strength in Soils Reinforced with Synthetic Fibers - Briceño Balza , Johannes Enrique (2025)
An important parameter to consider when designing civil works is the tensile strength of the soil. This parameter is often neglected because it has a lower value than the compressive strength induced by shear stresses, a parameter that determines the design. There are particular cases where tensile strength is important because it shows the first signs of soil failure and serves as a warning before shear failure occurs. Knowing this, to improve tensile resistance, it is proposed to reinforce the floor with synthetic fibers, micro and macrofibers, incorporating them in percentages by weight of soil (0.50, 1.00, 1.50 and 2.00%), evaluating the behavior through the indirect traction test of the natural and reinforced silty sandy soil. When comparing the results in these two conditions, it was concluded that the tensile strength increases when the percentage of macrofiber is greater than 1.50% by 3.69%, while at 2.00% it increases by 24.00% with respect to the soil pattern.